Performance analysis for three cases of outage probability in one-way DF full-duplex relaying network with presence of direct link - Phu Tran Tin; Van-Duc Phan; Le Anh Vu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
In this paper, the one-way decode-and-forward (DF) full-duplex relaying network system with presence of direct link is investigated. In the analysis section, we derived the exact, lower, and upper bound for outage probability (OP) with maximal ratio combining (MRC) at the receiver. Furthermore, the system performance's analytical expressions are verified by using the Monte Carlo simulation. In addition, we investigated the effect of the main parameters on the OP of the proposed system. Finally, we can sate that the simulation curves overlap the analytical curves to convince the analysis section. This research can provide a novel recommendation for the communication network.